Triazine-free polyimide for photocatalytic hydrogen production. (15th May 2023) - Xu, Xiaoyu; Wang, Xintie; Shao, Jingjing; Hong, Longfei; Zhang, Huiyan; Chu, Sheng
Abstract: Polyimide (PI) has received considerable attention as a promising donor-acceptor polymer for photocatalytic hydrogen production, yet the previous studies entirely focused on the exploration of triazine-based PI. Herein, we report for the first time triazine-free PI for photocatalytic hydrogen evolution. The triazine-free PI was synthesized by thermal condensation of urea and pyromellitic dianhydride. The resultant PI photocatalyst yielded a stable hydrogen evolution activity and an appreciable photocurrent response. This work manifests that triazine is not an indispensable unit for the photocatalytic hydrogen evolution activity of PI, which expands the chemical library of PI photocatalysts and opens up new opportunities for designing efficient polymeric photocatalysts. Graphical abstract: We report for the first time that triazine-free PI synthesized by urea and pyromellitic dianhydride shows an appreciable photocatalytic activity for hydrogen evolution. Image 1 Highlights: Triazine-free polyimide was reported for photocatalytic hydrogen evolution for the first time. Theoretical calculations were performed to reveal the photoactive sites. The chemical library of polyimide photocatalyst was expanded.